Effects of Ant Mounds on the Plant and Soil Microbial Community in an Alpine Meadow of Qinghai–Tibet Plateau. (3rd May 2017) - Wang, Changting; Wang, Genxu; Wu, Pengfei; Rafique, Rashid; Zi, Hongbiao; Li, Xiangzhen; Luo, Yiqi
Abstract: Ants are important soil engineers, affecting the structure and function of ecosystems. To address the impacts of ants ( Camponotus herculeanus ) on the properties of an alpine meadow ecosystem of Qinghai–Tibet Plateau, we investigated the effects of ant mounds on plant biomass, soil physicochemical properties, microbial diversity, and functions. We found that the total biomass of plant community was significantly greater in ant mound periphery. Plant species richness in ant mounds was reduced compared with that of control plots without ant mounds. Significant changes in physicochemical properties of soil were also observed. Soil organic matter, total nitrogen, available phosphorous, total potassium, and available potassium increased in ant mound soil due to the excavation activities by ants as well as the accumulation of organic matter and other nutrients during mound construction. For example, roots/soil contents (g/g) and soil moisture in ant mound soils were lower than those in controls. Microbial community composition and microbial biomass were clearly changed in ant mound soils. BIOLOG analysis further indicated that the functional diversity of the microbial community of ant mound soil increased and differed from that of controls. This study indicates that ant‐induced modification of soil properties indirectly influences plant biomass and species composition, and ant mounds have different microbial communities from those of control soil. Copyright © 2016 John Wiley & Sons, Ltd.